Strategies for integrating literature into teaching english as a foreign language for beginners. Application throgh aesop´s fables - Mendoza E., María Esther
This proposal presents strategies for teaching English as a foreign language for beginners using Aesop?s fables as a pedagogical resource. Communication is the new organizing principle for the EFL classroom; however, it also demands knowledge of certain linguistic and learning principles that guide language development. The Generative Grammar of Noam Chomsky explains us how the speakers-listeners of a linguistic community are able to communicate and interpret utterances using an innate competence. Besides, learning and psychological theories such as: Howard Gardner?s Multiple Intelligences (MI) theory, Jean Piaget?s Theory of Cognitive Development, and Abraham Maslow?s Hierarchy of needs allow us to develop adequate strategies for the students? level, preferences, and needs. Fables have been regarded as moral tales for children for a long time, but they may be useful in an EFL setting due to their didactic nature. They present the language in such a way that students? attention istrapped. Finally, a practical model of three lesson plans finishes this proposal.